2017
DOI: 10.4172/2329-8863.1000265
|View full text |Cite
|
Sign up to set email alerts
|

Why do Smallholder Farmers Apply Inorganic Fertilizers below the Recommended Rates? Empirical Evidence from Potato Production in Eastern Ethiopia

Abstract: Evidences suggested that use levels of inorganic fertilizers in potato production in Ethiopia are below the recommended rates. This study is aimed at accessing factors contributing to this. The study utilized data collected from 171 randomly selected potato producing households. A two-limit Tobit model result revealed that variation in districts, access to irrigation, frequency of extension contact, and livestock holding significantly affected intensity of adoption of both DAP and Urea in potato production. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Soil fertility is one of the factors that limit agricultural productivity in Ethiopia (Amare et al, 2018;Hirpa et al, 2012;Kebede and Ketema, 2017). Applying the right nutrient at the recommended rate, at the right time in the growing season and in the right place is essential for optimising the use of nutrients by crops (Chathurika et al, 2014;Ferguson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Soil fertility is one of the factors that limit agricultural productivity in Ethiopia (Amare et al, 2018;Hirpa et al, 2012;Kebede and Ketema, 2017). Applying the right nutrient at the recommended rate, at the right time in the growing season and in the right place is essential for optimising the use of nutrients by crops (Chathurika et al, 2014;Ferguson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Fertilizer is one of the most important inputs, which improve agricultural productivity substantially. However, evidence suggests that adoption of fertiliser and its intensity of application in Ethiopia is below the required level (Abrha, 2015; Kebede & Ketema, 2017). As shown in Table 1, the average use of chemical fertiliser for the previous three decades was found to be very low with mean value of 14.13 kg/ha.…”
Section: Methodsmentioning
confidence: 99%
“…Ketema and Kebede [29] indicated by study result revealed that variation in districts, family size, membership to cooperatives, distance to farmers training centre, and livestock holding significantly affected smallholders' intensity of adoption of DAP in maize production. On the other side, variation in district, farming experience, farm size, membership to cooperatives, dependency ratio, and annual income significantly determined intensity of adoption of Urea.…”
Section: Review In Technology Adoption Of Cereal Crops In Ethiopiamentioning
confidence: 96%